2005
DOI: 10.1038/sj.bjc.6602778
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human papillomavirus DNA gene sequences in human breast cancer

Abstract: Human papilloma viruses (HPVs) are accepted as being carcinogenic in human cervical and anogenital cancers. The suspicion that HPVs may also have a role in human breast cancer is based on the identification of HPVs in human breast tumours and the immortalisation of normal human breast cells by HPV types 16 and 18. For this investigation, DNA that had been previously extracted and fresh frozen at À701C from 50 unselected invasive ductal breast cancer specimens were screened by polymerase chain reaction (PCR) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 8 publications
8
107
3
3
Order By: Relevance
“…Different hypotheses can be envisaged to explain these findings. It is possible that the most frequently detected HPV types in the DL fluids (9,22,23 and 38) are present on the skin of the nipple at a higher copy number than the other beta HPVs. Therefore, they have a higher probability than the others to be transported by the catheter into or infect the ducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different hypotheses can be envisaged to explain these findings. It is possible that the most frequently detected HPV types in the DL fluids (9,22,23 and 38) are present on the skin of the nipple at a higher copy number than the other beta HPVs. Therefore, they have a higher probability than the others to be transported by the catheter into or infect the ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Low or high prevalence of HPV DNA in breast cancer of women was found in several studies. HPV16 or HPV18 were preferentially found in European women, while other types, e.g., 33, were frequently found in Japanese and Chinese cohorts [6][7][8][9][10][11][12][13][14][15][16]. De Villiers et al have recently shown that a broad spectrum of mucosal and cutaneous HPV types could be found in breast specimens using several PCR-based methods [16].…”
Section: Introductionmentioning
confidence: 99%
“…There were no differences in the average of age of women with either HPV-positive and -negative breast cancer in a study of Brazilian women (Damin et al, 2004). This is in contrast to a recent study of Greek women in which those with HPV-positive breast cancer were of average age 38 years as compared to average age 53 years for women with HPV-negative breast cancer (P-values for difference ¼ 0.001) (Kroupis et al, 2006).We have reviewed the ages of Australian women with HPVpositive and -negative breast cancer in our study published in this Journal (Kan et al, 2005). These data are shown in Table 1.…”
mentioning
confidence: 83%
“…High-risk HPVs of the same type have been identified in both cervical and breast cancer that had occurred in the same women (Hennig et al, 1999;Widschwendter et al, 2004). This observation has lead to the hypothesis that HPVs may be transmitted to the breast during sexual activities (Kan et al, 2005). If this hypothesis is correct, it is likely that HPV-positive breast cancers would occur in women younger than those with HPV-negative breast cancer.…”
Section: Sirmentioning
confidence: 98%
See 1 more Smart Citation